Microplastic content of three types of economically fish in the Industrial Area Waters of North Aceh and Lhokseumawe Regency - Muliari Muliari; Mahdaliana Mahdaliana; Irfannur Irfannur; Hizrah Ayumi Sitanggang; Yusrizal Akmal; M. Radhi; Salahuddin Salahuddin; Afrina Afrina; Agung Setia Batubara (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2025)
North Aceh and Lhokseumawe Regency are promising regions in the marine and fisheries industry, encompassing both big pelagic and small pelagic fish. The industrial zone in North Aceh and Lhokseumawe Regency is characterized by significant activity, where activity pertains to both industrial operations in the region and activities in coastal zones. The current industries include PT Pupuk Iskandar Muda, PT ASEAN Aceh Fertilizer, PT Kertas Kraft Aceh, and PT Arun Natural Gas Liquefaction. Identifying microplastics in economically important fish in industrial area waters is necessary to determine whether the fish contain microplastics. The aim of this research is to determine the microplastic content in three economically fish, namely trevally (Caranx ignobilis), grouper (Epinephelus fuscoguttatus), and mackerel (Rastrelliger sp.). The research was carried out in 2024. Data and samples were collected using a survey method taken directly in the field. The data collection points during the research were at four locations around the industrial area, namely PT Pupuk Iskandar Muda (station 1), PT ASEAN Aceh Fertilizer (station 2), PT Kertas Kraft Aceh (station 3), PT Arun Natural Gas Liquefaction (station 4) in the waters of North Aceh and Lhokseumawe Regency. Analysis of microplastic content was carried out at the Oceanography Laboratory, Faculty of Agriculture, Malikussaleh University. Based on research results, the types of microplastics found in the digestive organs of trevally, grouper and mackerel are fiber, film, fragments, granules, pellets, and foam. Frequency value of microplastics found at the research location from the four stations, where the most dominant found was the foam type (35.96%) on trevally, fiber type (22.59%) on grouper, and fiber type (35.19%) on mackerel.